Respuestas

  • Usuario de Brainly
2012-10-18T00:03:09+02:00

2x ^ 2 - 4x - 4 = 2 
2x ^ 2 - 4x - 6 = 0 
x ^ 2 - 2x - 3 = 0 
(x - 3) (x + 1) = 0 x - 3 = 0 x = 3 o x + 1 = 0 x = -1 lo que las dos soluciones son x = -1, 3.

asi se cumple  >0 
porque x=1>0
          x=3>0 

2012-10-18T00:17:00+02:00

2x ^ 2 - 4x - 4 = 2 
2x ^ 2 - 4x - 6 = 0 
x ^ 2 - 2x - 3 = 0 
(x - 3) (x + 1) = 0 x - 3 = 0 x = 3 o x + 1 = 0 x = -1 lo que las dos soluciones son x = -1, 3.

asi se cumple  >0 
porque x=1>0
          x=3>0